Alteration of patterns of endocrine response during a competitive swim training session - Neisler, H. M.; Bean, M. H.; Thompson, W. R. (Biomechanics and Medicine in Swimming. Swimming Science VI, 1992)
Endocrine responses to swim training across an entire training season were followed in 17 male collegiate competitive swimmers X age 19.7 ± 1.3 years). Venous blood samples were collected immediately before (PRE) and upon completion (PS) of seven typical early morning swim workouts at intervals during the season. Serum cortisol (COR), growth hormone (hGH), prolactin {PRO), thyroid stimulating hormone (TSH), triiodothyronine (T3), thyroxine (T4) and T3 uptake (T3U) were measured by radioimmunoassay or enzyme immunoassay procedures. Neither height, weight, % body fat, hGH or T3 changed significantly across the PRE samples but significant changes across time occurred in all other PRE analytes. The pattern of PRE to PS COR, PRO and TSH changed significantly during the period of greatest training stress while the response of the other analytes remained relatively consistent across the season. Increases in self-reported physical and psychological stress paralleled alterations of COR, PRO and TSH. These changes in pattern of PRE to PS analytes demonstrate the importance of cumulative training effects when evaluating single endocrine samples.